The Development of Blog with Nos Within Inquiry Laboratory an Approach for Developing Scientific Literacy of the Student in Junior High School - Widowati, A; Atun, S; Suryadarma, IGP; ., Setuju; Widodo, E; Nurohman, S; E.K Yuneivi, R (International Journal of Engineering and Technology, 2018)
The era of industry 4.0 requires Indonesia's quality human resources superior, but there are a big problem that many students have low of scientific literacy. Efforts to instill scientific literacy can help students develop an informed conception of the nature of science (NOS) by using a progressive and authentic learning inquiry environment. This research investigate about how is the blog with NOS within inquiry laboratory model that is eligible to develop scientific literacy in science learning of junior high school and the effectiveness of blog with NOS within inquiry laboratory model for developing scientific inquiry. This research is done by 4D Model in Research and Development. The Subject is expert in media and science content, and 68 students of SMP N 9 Yogyakarta. The design of playing field testing is quasi experiment with nonequivalent pretest-postest control group design. The research instruments are the questionnaire of product validation and the scientific literacy test. The data analyze with descriptive qualitative for the validation result and t-test for the scientific literacy test results. The results show that the blogs that produced in this research is eligible as learning media in NOS within inquiry laboratory model. There is a significant difference scientific literacy between before and after learning with and without using blog in NOS within inquiry laboratory modelÂ